Era Digital dalam Perspektif Islam: Urgensi Etika Komunikasi Umat Beragama di Indonesia - Wida Fitria; Ganjar Eka Subakti (Universitas Islam Negeri (UIN) Mataram, 2022)
The development of technology, information and communication has grown rapidly marked by the Industrial Revolution 4.0 and the Social Revolution 5.0 in various digital platforms. The role of Islam in responding to the digital era is used as a solution to the problems studied. This study aims to describe and analyze the problems and solutions in maintaining communication on digital media from an Islamic perspective. The research method used is qualitative with a descriptive approach through a literature review from several scientific sources related to Islam and technology. The research focuses on analyzing communication problems on social media and their solutions through communication ethics based on an Islamic perspective. The results show that Islam emphasizes religious people to maintain and build good inter-religious communication. This research study is expected to be useful for religious leaders in adapting to technological developments in the digital era.